Echocardiographic sign of right-sided hypertrophic obstructive cardiomyopathy. Issue 11 (November 1978) - Cardiel, E A; Alonso, M; Delcan, J L; Menarguez, L
Abstract : The echocardiographic and haemodynamic findings with a patient with hypertrophic obstructive cardiomyopathy (HOCM) and dynamic subpulmonary stenosis, without left ventricular gradient, are described. The echocardiogram shows not only asymmetric septal hypertrophy, systolic anterior movement of the anterior mitral leaflet, and midsystolic collapse of the aortic valve, but also increase in the right ventricular wall echoes and systolic collapse of the pulmonary valve. We believe that in the absence of pulmonary hypertension these signs, particularly the systolic closing movement of the pulmonary valve cusp, may suggest right ventricular obstruction in HOCM.